Enhancing Cognitive Function in People with Mental Disorders Using Snakes Ladders and Crossword Puzzles - Hartono, Dudi; Pancani, Peni Cahyati Teguh; Destiana, Nasha Tri; Saputri, Aprianti Dewi; Lestari, Evi Sri (International Journal Scientific and Professional, 2025)
Mental disorders often bring significant cognitive impairments, which can hinder daily functioning and the overall quality of life. This research explores the effectiveness of using Snakes and Ladders and crossword puzzles as cognitive therapy tools for individuals with mental disorders. These games, although simple, engage various cognitive processes such as memory, attention, problem-solving, and logical thinking. The study employed a pre-and post-intervention design to assess the cognitive improvements in participants who engaged in structured game-based therapy over several weeks. Before the intervention, cognitive function was evaluated using the Montreal Cognitive Assessment (MoCA), showing signs of cognitive impairment in most participants; after the therapy sessions, which included regular play of Snakes and Ladders and crossword puzzles, a significant improvement was observed in participants' cognitive abilities, with average MoCA scores rising from 18 to 22. This improvement reflected better short-term memory, concentration, and problem-solving skills. The games also fostered increased social interaction and collaboration among participants, contributing to emotional well-being and reducing anxiety. The results highlighted decreased stress and anxiety, as participants reported feeling more relaxed and engaged after several sessions. The study concludes that cognitive therapy based on simple, accessible games like Snakes and Ladders and crossword puzzles can effectively enhance cognitive function, reduce anxiety, and improve social skills in people with mental disorders. The findings suggest that such game-based therapy could be a valuable, low-cost alternative to traditional cognitive remediation therapies in community settings.